Estimation of Ship Domain Zone - Švetak, Jelenko (Promet - Traffic&Transportation, 2009)
The paper discusses the ship domain zone or ship navigationsafety area. The navigation safety area around the ship hasbeen the object of research of many authors. Different variantsand algorithms have been suggested and the most popularamong them are as follows:- navigation safety area around the ship being observed by herown devices, presenting information of the danger of possiblecollision directly on the bridge;- navigation safety area around the ship when regulating hermovement by means of Vessel Traffic Se1vices.The article presents an algorithm for determination andplotting of the navigation safety area, which has the followingadvantages:- the algorithms give an instant solution to the problem ofevading one or more dangerously moving targets;- the calculation may apply the ARPA (Automatic RadarPlotting Aids) algorithm, which does not prevent the navigatorfrom keeping watch.The above mentioned algorithm allows simultaneous plottingof information about the situation around the ship and thedata for probable manoeuvring.